A trajetória e as colunas cinematográficas de Ironides Rodrigues para a marcha (1954-1962) - Predebon, Gabriel Soares (2019)
This study aims to analyze the cinematographic columns that Ironides Rodrigues (1923-1987) wrote for the newspaper A Marcha, the official organ of the Partido de Representação Popular, of conservative tendencies and political heir of Ação Integralista Brasileira, fascist inspired movement of the 1930’s. It aims to comprehend, through the author’s trajectory, marked by his involvement within the Black Movement, mainly the Teatro Experimental do Negro, funded by Abdias Nascimento, the relations between integralism and the racial question, as his political tendencies and catholic faith. Through his cinematographic columns, the study aims to analyze the author’s insertion in the cinematographic criticism, Besides the Catholicism that in his columns, its distances and approximations with the organized groups in relation to cinema and the presence of the racial question in his columns.